Cancer Biomarkers in the era of precision oncology: Addressing the needs of patients and health systems. (September 2022) - Normanno, Nicola; Apostolidis, Kathi; de Lorenzo, Francesco; Beer, Philip A.; Henderson, Raymond; Sullivan, Richard; Biankin, Andrew V.; Horgan, Denis; Lawler, Mark
Abstract: Cancer Biomarkers are the key to unlocking the promise of precision oncology, selecting which patients will respond to a more personalised treatment while sparing non-responders the therapy-related toxicity. In this paper, we highlight the primacy of cancer biomarkers, but focus on their importance to patients and to health systems. We also highlight how cancer biomarkers represent value for money. We emphasise the need for cancer biomarkers infrastructure to be embedded into European health systems. We also highlight the need to deploy multiple biomarker testing to deliver the optimal benefit for patients and health systems and consider cancer biomarkers from the perspective of cost, value and regulation. Cancer biomarkers must also be situated in the context of the upcoming In Vitro Diagnostics Regulation, which may pose certain challenges (e.g. non-compliance of laboratory developed tests, leading to cancer biomarker shortages and increased costs) that need to be overcome. Cancer biomarkers must be embedded in the real world of oncology delivery and testing must be implemented across Europe, with the intended aim of narrowing, not widening the inequity gap for patients. Cancer patients must be placed firmly at the centre of a cancer biomarker informed precision oncology care agenda.